Application of iodine-containing conductive ion additive in sulfur positive electrode of solid-state lithium-sulfur battery, positive electrode material as well as preparation method and application of positive electrode material

By introducing iodine-containing ion-conducting additives into the sulfur positive electrode of solid-state lithium-sulfur batteries, the oxidation of Li2S is promoted by using its redox activity, and the problems of poor rate performance and cycle life of solid-state lithium-sulfur batteries are solved, and high specific capacity, fast charging performance and cycle stability are achieved.

CN119695158AActive Publication Date: 2025-03-25PEKING UNIV

Patent Information

Application Number
CN202411898999.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Solid-state lithium-sulfur batteries have poor rate performance and cycle life due to the slow solid-solid-sulfur oxidation and reduction reaction of elemental sulfur and lithium sulfide.

Method used

Iodine-containing ion-conducting additives are introduced, and their redox activity is used as a mediator to promote the oxidation of Li2S and improve the reaction kinetics of Li2S in the sulfur cathode.

Benefits of technology

Through the redox mediation strategy, the specific capacity and fast charging performance of solid-state lithium-sulfur batteries are improved, and the continuous degradation of iodine-containing ion-induced additives is avoided through reversible redox reactions, and the cycle stability of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695158A_ABST
    Figure CN119695158A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state lithium-sulfur batteries, in particular to application of an iodine-containing conductive ion additive in a sulfur positive electrode of a solid-state lithium-sulfur battery, a positive electrode material as well as a preparation method and application of the positive electrode material. The iodine-containing guide ion additive is used as a redox mediating agent to promote Li2S oxidation, I <-> in the iodine-containing guide ion additive is electrochemically oxidized into iodine in an oxidation state on a conductive material interface of the iodine-containing guide ion additive during charging, and then the iodine in the oxidation state chemically oxidizes Li2S in contact with the iodine in the oxidation state. On the basis of a redox mediation process on the surface of the iodine-containing guide ion additive, the reaction on a Li2S two-phase interface of the iodine-containing guide ion additive is carried out, so that the solid reaction kinetics of sulfur is improved; the iodine-containing guide ion additive comprises a compound containing iodine, lithium and sulfur elements, and the molar weight of the iodine element in each mole of the iodine-containing guide ion additive is 0 lt; nI < = 2. The iodine-containing conductive ion additive enables the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery prepared from the sulfur positive electrode to have fast charge performance and high cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state lithium-sulfur batteries, and in particular to the application of an iodine-containing ion-conducting additive in a sulfur positive electrode of a solid-state lithium-sulfur battery, a positive electrode material and a preparation method and application thereof; more particularly, it relates to the application of an iodine-containing ion-conducting additive in a sulfur positive electrode of a solid-state lithium-sulfur battery, a positive electrode material for a solid-state lithium-sulfur battery and a preparation method thereof, a solid-state lithium-sulfur battery and electrical equipment. Background Art

[0002] With the widespread application of renewable energy such as solar energy and wind energy, lithium batteries play a key role as an important component of energy storage systems. They can balance the difference between power generation and demand and improve energy utilization efficiency. With the rapid development of information technology, mobile communications and electric vehicles, the global demand for high energy density and long life batteries continues to increase. Lithium batteries have become the main solution to meet these needs with their superior energy density and power density. All-solid-state batteries are more competitive in electric vehicles and high energy demand applications due to their high safety and high energy density. All-solid-state batteries based on layered metal oxide cathodes are currently receiving widespread attention, but under high pressure, irreversible side reactions between layered metal oxide cathodes and electrolytes and chemical mechanical degradation of nickel-rich layered metal oxides hinder their long-term stability and rate performance. All-solid-state lithium-sulfur batteries have higher intrinsic safety because their appropriate potential does not cause further side reactions of solid electrolytes and charging does not release reactive oxygen. In addition, solid-state lithium-sulfur batteries using solid electrolytes eliminate the thorny polysulfide shuttle phenomenon in liquid lithium-sulfur batteries.

[0003] The sulfur cathode has a large theoretical capacity (1672 mAh g -1 ), which can meet application scenarios with high energy requirements. At the same time, sulfur is a material with high abundance and low price. Compared with rare metals such as cobalt and nickel used in lithium-ion batteries, the material cost of lithium-sulfur batteries is low and suitable for large-scale production. Moreover, lithium-sulfur batteries do not produce heavy metal pollution during use, and the environmental protection treatment after disposal is relatively easy, which meets the requirements of green and sustainable development. The multiple advantages of sulfur positive electrode make it a promising battery material.

[0004] However, solid-state lithium-sulfur batteries suffer from poor rate performance and cycle life due to the slow solid-solid sulfur redox reaction of elemental sulfur and lithium sulfide. Since both active materials (sulfur and lithium sulfide) are electronic insulators, the reaction can only occur at the three-phase boundary between the solid electrolyte, active material and carbon. The density of three-phase boundary sites is usually much lower than that of two-phase boundary sites, so the reaction space is greatly limited, which poses a challenge to effective solid-solid charge transfer. The prior art has made a series of important attempts by introducing functional additives (such as Cu, LiVS2 and modified carbon) into the positive electrode, but the kinetic problems caused by the "all-solid three-phase boundary" have not been fully solved. At the same time, due to the large volume change of sulfur during charging and discharging and the complex solid-solid contact interface, the current all-solid-state lithium-sulfur batteries have a short cycle life.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first object of the present invention is to provide an application of an iodine-containing ion-conducting additive in a sulfur positive electrode of a solid-state lithium-sulfur battery, wherein the iodine-containing ion-conducting additive contains an I element with redox activity, which can act as a redox mediator to promote the oxidation of Li2S. Specifically, during fast charging, the I in the iodine-containing ion-conducting additive is - It can be electrochemically oxidized to oxidized iodine at the electrolyte | conductive material interface, and then the oxidized iodine will chemically oxidize the Li2S in contact with it. The reaction of oxidized iodine and Li2S has ultra-fast reaction kinetics, and the physical contact between the two can produce a relatively fast chemical reaction. Therefore, the redox of iodine in the iodine-containing ion-conducting additive greatly improves the reaction kinetics of Li2S in the sulfur positive electrode. Moreover, this redox-mediated process based on the surface of the iodine-containing ion-conducting additive allows the solid-state conversion reaction of sulfur to proceed at the two-phase boundary of the iodine-containing ion-conducting additive | Li2S (this boundary is usually inactive in other solid-state lithium-sulfur batteries), and the contact range of the two-phase boundary is larger than that of the three-phase boundary of the iodine-containing ion-conducting additive | Li2S | conductive material. Through this redox-mediated strategy, the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery made thereof have excellent specific capacity and fast charging performance. In addition, the reversible redox reaction of the iodine-containing ion-conducting additive avoids the continuous degradation of the iodine-containing ion-conducting additive, so that the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery made thereof have excellent cycle stability. Therefore, the problems of poor rate performance and cycle life of conventional solid-state lithium-sulfur batteries are solved.

[0007] The second object of the present invention is to provide a positive electrode material for a solid-state lithium-sulfur battery, which can achieve the fast charging capability of the solid-state lithium-sulfur battery by introducing a specific type of iodine-containing ion-conducting additive. Specifically, the iodine-containing ion-conducting additive contains an I element with redox activity, which can act as a redox mediator to promote the oxidation of Li2S. During fast charging, the I in the iodine-containing ion-conducting additive is - It can be electrochemically oxidized to oxidized iodine at the electrolyte | conductive material interface, and then the oxidized iodine will chemically oxidize the Li2S in contact with it. The reaction of oxidized iodine with Li2S has ultra-fast reaction kinetics, and the two can undergo a relatively fast chemical reaction when they are in physical contact. Therefore, the redox of iodine in the iodine-containing ion-conducting additive greatly improves the reaction kinetics of Li2S in the sulfur positive electrode. Moreover, this redox-mediated process based on the surface of the iodine-containing ion-conducting additive allows the solid-state conversion reaction of sulfur to proceed at the two-phase boundary of the iodine-containing ion-conducting additive | Li2S (this boundary is usually inactive in other solid-state lithium-sulfur batteries), and the contact range of the two-phase boundary is larger than that of the three-phase boundary of the iodine-containing ion-conducting additive | Li2S | conductive material. Through this redox-mediated strategy, the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery prepared therefrom have excellent specific capacity and fast charging performance. At the same time, the introduction of iodine-containing ion-conducting additives can achieve high cycle stability of solid-state lithium-sulfur batteries. Specifically, the reversible redox reaction of the iodine-containing ion-conducting additive avoids the continuous degradation of the iodine-containing ion-conducting additive, so that the solid-state lithium-sulfur battery sulfur positive electrode and the battery prepared therefrom have excellent cycle stability.

[0008] The third object of the present invention is to provide a method for preparing a positive electrode material for a solid-state lithium-sulfur battery, wherein the positive electrode material prepared by the method has high rate performance, fast charging capability and excellent cycle stability.

[0009] A fourth object of the present invention is to provide a solid-state lithium-sulfur battery having fast charging capability, high cycle stability and high energy density.

[0010] A fifth object of the present invention is to provide an electrical device.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] The present invention first provides an application of an iodine-containing ion-conducting additive in a sulfur positive electrode of a solid-state lithium-sulfur battery, wherein the iodine-containing ion-conducting additive acts as a redox mediator to promote the oxidation of Li2S, wherein during charging, I -At the interface between the iodine-containing ion-conducting additive and the conductive material in the sulfur cathode, iodine is electrochemically oxidized to the oxidized state. Subsequently, the oxidized iodine chemically oxidizes the Li2S in contact therewith. Based on the redox-mediated process on the surface of the iodine-containing ion-conducting additive, the reaction at the iodine-containing ion-conducting additive|Li2S two-phase interface can proceed, thereby improving the solid-state reaction kinetics of sulfur. The iodine-containing ion-conducting additive includes a compound containing at least iodine, lithium, and sulfur elements, and the molar amount n of the iodine element in each mole of the iodine-containing ion-conducting additive I is 0 < n I ≤ 2.

[0013] Furthermore, the iodine-containing ion-conducting additive includes at least one compound among Formula (1), Formula (2), Formula (3), Formula (4), Formula (5), Formula (6), and Formula (7):

[0014] Formula (1): Li 2+y+z B 2x S 1+3x I y X z , where 0.15 ≤ x ≤ 4, 0 < y ≤ 2, 0 ≤ z ≤ 2, 0.05 ≤ y + z ≤ 2, and X includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN.

[0015] Formula (2): Li 2+y P 2d S 1+5d I y , where 0.2 ≤ d ≤ 0.5, 0 < y ≤ 2.

[0016] Formula (3): Li 2+y P 2e Q 2f S 1+5e+5f I y , where 0.2 ≤ e ≤ 0.5, 0 < f ≤ 0.3, 0 < y ≤ 2, and Q includes at least one of As, Sb, and Bi elements.

[0017] Formula (4): Li 2+y P 2s Z g S 1+5s+2g I y , where 0.2 ≤ s ≤ 0.5, 0 < g ≤ 0.15, 0 < y ≤ 2, and Z includes at least one of Si, Ge, and Sn elements.

[0018] Formula (5): Li 2+y+c B 2b M 2a S 1+3b+5a I y A c, where 0.15 ≤ b ≤ 3, 0.05 ≤ a ≤ 3, 0.25 ≤ b + a ≤ 4, 0 < y ≤ 2, 0 ≤ c ≤ 2, 0 ≤ y + c ≤ 2, M includes at least one of P, As, Sb, and Bi, and A includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN.

[0019] Formula (6): Li 6-h PS 5-h Cl 1+h-y I y , where 0 ≤ h ≤ 2, 0 < y ≤ 2, 1 + h - y ≥ 0.

[0020] Formula (7): Li 6-m PS 5-m Cl 1+m-n-y Br n I y , where 0 ≤ m ≤ 2, 0 ≤ n ≤ 2, 0 < y ≤ 2, 1 + m - n - y ≥ 0.

[0021] Furthermore, in the said formula (1), 0.25 ≤ x ≤ 2, 0.01 ≤ y ≤ 2, 0.01 ≤ y + z ≤ 2.

[0022] Furthermore, in the said formula (2), 0.25 ≤ d ≤ 0.5, 0.01 ≤ y ≤ 2.

[0023] Furthermore, in the said formula (3), 0.25 ≤ e ≤ 0.5, 0 < f ≤ 0.25, 0.01 < y ≤ 2.

[0024] Furthermore, in the said formula (4), 0.25 ≤ s ≤ 0.5, 0 < g ≤ 0.125, 0.01 < y ≤ 2.

[0025] Furthermore, in the said formula (5), 0.25 ≤ b ≤ 2, 0.05 ≤ a ≤ 2, 0.3 ≤ b + a ≤ 3, 0.01 ≤ y ≤ 2, 0.01 ≤ y + c ≤ 2.

[0026] Furthermore, in the said formula (5), 0.25 ≤ b ≤ 1.5, 0.05 ≤ a ≤ 1, 0.3 ≤ b + a ≤ 2.5, 0.01 ≤ y ≤ 2, 0 ≤ c ≤ 2, 0.01 ≤ y + c ≤ 2.

[0027] Furthermore, in the said formula (6), 0 ≤ h ≤ 1, 0.01 ≤ y ≤ 2, 1 + h - y > 0.

[0028] Furthermore, in the said formula (7), 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0.01 ≤ y ≤ 2, 1 + m - n - y > 0.

[0029] Further, the sulfur cathode of the solid-state lithium-sulfur battery further includes a sulfur-containing active material, and the sulfur-containing active material includes at least one of sulfur, sulfur-selenium alloy, composite material of sulfur and carbon material, composite material of sulfur and metal sulfide, Li2S, composite material of Li2S and carbon material, composite material of Li2S and LiI, and composite material of Li2S and metal sulfide.

[0030] Further, the sulfur cathode of the solid-state lithium-sulfur battery further includes a conductive carbon additive.

[0031] Further, the mass ratio of the sulfur-containing active material, the iodine-containing ion-conducting additive, and the conductive carbon additive is 30-95:5-70:0-50.

[0032] The present invention further provides a cathode material for a solid-state lithium-sulfur battery. The cathode material includes an iodine-containing ion-conducting additive, and the molar amount n of iodine element in each mole of the iodine-containing ion-conducting additive I is 0 < n I ≤ 2. The iodine-containing ion-conducting additive includes at least one compound of formula (1), formula (2), formula (3), formula (4), formula (5), formula (6), and formula (7):

[0033] Formula (1): Li 2+y+z B 2x S 1+3x I y X z , where 0.15 ≤ x ≤ 4, 0 < y ≤ 2, 0 ≤ z ≤ 2, 0.05 ≤ y + z ≤ 2, and X includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN.

[0034] Formula (2): Li 2+y P 2d S 1+5d I y , where 0.2 ≤ d ≤ 0.5, 0 < y ≤ 2.

[0035] Formula (3): Li 2+y P 2e Q 2f S 1+5e+5f I y , where 0.2 ≤ e ≤ 0.5, 0 < f ≤ 0.3, 0 < y ≤ 2, and Q includes at least one of As, Sb, and Bi elements.

[0036] Formula (4): Li 2+y P 2s Z g S 1+5s+2g I y, where 0.2 ≤ s ≤ 0.5, 0 < g ≤ 0.15, 0 < y ≤ 2, and Z includes at least one of Si, Ge, and Sn elements.

[0037] Formula (5): Li 2+y+c B 2b M 2a S 1+3b+5a I y A c , where 0.15 ≤ b ≤ 3, 0.05 ≤ a ≤ 3, 0.25 ≤ b + a ≤ 4, 0 < y ≤ 2, 0 ≤ c ≤ 2, 0 ≤ y + c ≤ 2, M includes at least one of P, As, Sb, and Bi, and A includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN.

[0038] Formula (6): Li 6-h PS 5-h Cl 1+h-y I y , where 0 ≤ h ≤ 2, 0 < y ≤ 2, and 1 + h - y ≥ 0.

[0039] Formula (7): Li 6-m PS 5-m Cl 1+m-n-y Br n I y , where 0 ≤ m ≤ 2, 0 ≤ n ≤ 2, 0 < y ≤ 2, and 1 + m - n - y ≥ 0.

[0040] Furthermore, the positive electrode material further includes a sulfur-containing active material.

[0041] Furthermore, the sulfur-containing active material includes at least one of sulfur, sulfur-selenium alloy, composite of sulfur and carbon material, composite of sulfur and metal sulfide, Li2S, composite of Li2S and carbon material, composite of Li2S and LiI, and composite of Li2S and metal sulfide.

[0042] Furthermore, the positive electrode material further includes a conductive carbon additive.

[0043] Furthermore, the mass ratio of the sulfur-containing active material, the conductive carbon additive, and the iodine-containing ion-conducting additive is 30 - 95: 0 - 50: 5 - 70.

[0044] Furthermore, the conductive carbon additive includes at least one of Ketjen black, conductive carbon black, vapor-grown carbon fiber reinforcement, carbon nanotube, mesoporous carbon, microporous carbon, graphene, and acetylene black.

[0045] The present invention further provides a method for preparing the positive electrode material for a solid-state lithium-sulfur battery, comprising the following steps: mixing an iodine-containing ion-conducting additive with a sulfur-containing active material, or mixing an iodine-containing ion-conducting additive with a sulfur-containing active material and a conductive carbon additive.

[0046] Furthermore, the mixing method includes at least one of grinding, ball milling, vibration milling and high-speed stirring.

[0047] The present invention further provides a solid-state lithium-sulfur battery, comprising the positive electrode material for the solid-state lithium-sulfur battery.

[0048] Furthermore, the solid-state lithium-sulfur battery also includes a solid electrolyte separator and a negative electrode.

[0049] Further, the negative electrode includes at least one of lithium metal, lithium alloy, graphite, silicon, silicon-carbon composite material, silicon oxide and lithium carbon material;

[0050] Furthermore, the solid electrolyte separator includes at least one of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte, a polymer electrolyte, a sulfide-polymer composite electrolyte, a halide-polymer composite electrolyte and an oxide-polymer composite electrolyte.

[0051] The present invention also provides an electrical device, comprising the solid-state lithium-sulfur battery.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The present invention provides an application of an iodine-containing ion-conducting additive in a sulfur positive electrode of a solid-state lithium-sulfur battery, and uses the iodine-containing ion-conducting additive to achieve fast charging capability of a solid-state lithium-sulfur battery. The iodine-containing ion-conducting additive contains an I element with redox activity, which can act as a redox mediator to promote the oxidation of Li2S. During fast charging, the I in the iodine-containing ion-conducting additive - It can be electrochemically oxidized to oxidized iodine at the electrolyte | conductive material interface, and then the oxidized iodine will chemically oxidize the Li2S in contact with it. The reaction of oxidized iodine with Li2S has ultra-fast reaction kinetics, and the reaction occurs with just a slight contact, which greatly improves the utilization rate of Li2S in the sulfur positive electrode. Moreover, this redox-mediated process based on the surface of the iodine-containing ion-conducting additive allows the reaction to proceed at the two-phase boundary of the iodine-containing ion-conducting additive | Li2S (this boundary is usually inactive in other solid-state lithium-sulfur batteries), and its contact range is larger than that of the three-phase boundary of the iodine-containing ion-conducting additive | Li2S | conductive material. Through this redox-mediated strategy, the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery made therefrom have excellent fast charging performance.

[0054] (2) The application of the iodine-containing ion-conducting additive provided by the present invention in the sulfur positive electrode of a solid-state lithium-sulfur battery, and the use of the iodine-containing ion-conducting additive to achieve high cycle stability of the solid-state lithium-sulfur battery. The reversible redox reaction of the iodine-containing ion-conducting additive avoids the continuous degradation of the iodine-containing ion-conducting additive, so that the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery prepared therefrom have excellent cycle stability.

[0055] (3) The positive electrode material for solid-state lithium-sulfur batteries provided by the present invention can achieve the fast charging capability of solid-state lithium-sulfur batteries by introducing a specific type of iodine-containing ion-conducting additive. Specifically, the iodine-containing ion-conducting additive contains an I element with redox activity, which can act as a redox mediator to promote the oxidation of Li2S. During fast charging, the I in the iodine-containing ion-conducting additive is - It can be electrochemically oxidized to oxidized iodine at the electrolyte | conductive material interface, and then the oxidized iodine will chemically oxidize the Li2S in contact with it. The reaction of oxidized iodine with Li2S has ultrafast reaction kinetics, and the reaction occurs with a slight contact, which greatly improves the utilization rate of Li2S in the sulfur positive electrode. In addition, this redox-mediated process based on the surface of the iodine-containing ion-conducting additive allows the reaction at the two-phase boundary of the iodine-containing ion-conducting additive | Li2S (this boundary is usually inactive in other solid-state lithium-sulfur batteries), and its contact range is larger than that of the three-phase boundary of the iodine-containing ion-conducting additive | Li2S | conductive material. Through this redox-mediated strategy, the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery made thereof have excellent fast charging performance. At the same time, the introduction of the iodine-containing ion-conducting additive can achieve high cycle stability of the solid-state lithium-sulfur battery. Specifically, the continuous degradation of the iodine-containing ion-conducting additive is avoided by the reversible redox reaction of the iodine-containing ion-conducting additive, so that the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery made thereof have excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0057] Figure 1 The long cycle test result of the all-solid-state lithium-sulfur battery prepared in Example 1 provided by the present invention at 25°C and a charge and discharge rate of 5C;

[0058] Figure 2 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 1 provided by the present invention;

[0059] Figure 3 The specific capacity test results of the all-solid-state lithium-sulfur battery prepared in Example 2 provided by the present invention at 60°C and different charge rates (fixed discharge rate is 2C);

[0060] Figure 4 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 2 provided by the present invention;

[0061] Figure 5 The long cycle test results of the all-solid-state lithium-sulfur battery prepared in Example 3 provided by the present invention;

[0062] Figure 6 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 3 provided by the present invention;

[0063] Figure 7 The long cycle test results of the all-solid-state lithium-sulfur battery prepared in Example 4 provided by the present invention;

[0064] Figure 8 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 4 provided by the present invention;

[0065] Fig. 9 The long cycle test results of the all-solid-state lithium-sulfur battery prepared in Example 5 provided by the present invention;

[0066] Fig.10 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 5 provided by the present invention;

[0067] Fig.11 The specific capacity test results of the all-solid-state lithium-sulfur battery prepared in Example 6 provided by the present invention at 25° C. and different charge rates (fixed discharge rate is 1C);

[0068] Fig.12 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 6 provided by the present invention;

[0069] Fig.13 The specific capacity test results of the all-solid-state lithium-sulfur battery prepared in Comparative Example 1 provided by the present invention at 60° C. and different charge rates (fixed discharge rate is 2C);

[0070] Fig.14 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Comparative Example 1 provided by the present invention;

[0071] Fig.15 The long cycle test results of the all-solid-state lithium-sulfur battery prepared in Comparative Example 2 provided by the present invention;

[0072] Fig.16The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Comparative Example 2 provided by the present invention;

[0073] Fig.17 The long cycle test results of the all-solid-state lithium-sulfur battery prepared in Comparative Example 3 provided by the present invention;

[0074] Fig.18 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Comparative Example 3 provided by the present invention;

[0075] Fig.19 The specific capacity test results of the all-solid-state lithium-sulfur battery prepared in Comparative Example 4 provided by the present invention at 25° C. and different charge rates (fixed discharge rate is 1C);

[0076] Fig. 20 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Comparative Example 4 provided by the present invention;

[0077] Fig.21 The XRD test results provided by the present invention prove that I2 and Li2S react with each other in physical contact;

[0078] Fig. 22 The Raman test results provided by the present invention prove that I2 reacts with Li2S in physical contact. DETAILED DESCRIPTION

[0079] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0080] In the first aspect, the present invention provides an application of an iodine-containing ion-conducting additive in a sulfur positive electrode of a solid-state lithium-sulfur battery, wherein the iodine-containing ion-conducting additive promotes the oxidation of Li2S as a redox mediator while conducting ions, wherein the I in the iodine-containing ion-conducting additive during charging - The interface between the iodine-containing ion-conducting additive and the conductive material in the sulfur positive electrode is electrochemically oxidized into oxidized iodine, and then the oxidized iodine chemically oxidizes the Li2S in contact with it. Based on the redox mediated process on the surface of the iodine-containing ion-conducting additive, the reaction at the iodine-containing ion-conducting additive|Li2S two-phase interface is carried out, thereby improving the solid-state reaction kinetics of sulfur.

[0081] The proof of the above principle is as follows: Fig.21 and Fig. 22 As shown. By simply and quickly hand-grinding and mixing I2 and Li2S solid powders, we demonstrated the rapid reaction of I2 and Li2S. Grinding equimolar amounts of I2 and Li2S solid powders in an agate mortar, hand-grinding for five minutes, and then performing XRD and Raman spectroscopy tests on the ground products ( Fig.21 and Fig. 22 ). XRD results show the formation of crystalline phase LiI ( Fig.21 ), Raman spectrum shows the generation of S signal, accompanied by I3 - The signal ( Fig. 22 ). This indicates that I2 and Li2S react to generate S and I through simple solid-solid contact. - and I3 - Therefore, this proves that during the charging process of the battery, the iodine-containing ion-conducting additive will be able to directly chemically oxidize the physically contacted Li2S, which provides strong evidence for the redox mediation effect in the battery.

[0082] Wherein, the above oxidation state of iodine refers to I2 and / or I3 - and / or other oxidized forms of iodine.

[0083] The above-mentioned conductive materials include any conductive materials commonly used in the art, such as materials containing metal elements (such as metal sulfides, alloys, etc.) and carbon materials (such as conductive graphite, carbon black, etc.). The source of the conductive material can be sulfur-containing active materials or conductive carbon additives, but is not limited to this.

[0084] The iodine-containing ion-conducting additive comprises a compound containing at least iodine, lithium and sulfur, and the molar amount of the iodine in each mole of the iodine-containing ion-conducting additive is n I is 0 <n I ≤2. Where n I Including but not limited to any one of 0.001, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or any range between two thereof. Wherein, the appropriate iodine content can make the iodine-containing ion-conducting additive have a suitable ion conductivity. If n I When the ratio is greater than 2, the ion-conducting ability of the iodine-containing ion-conducting additive may be reduced and / or the mass density of the electrolyte may be too large, thereby affecting the overall specific capacity of the sulfur positive electrode.

[0085] The present invention utilizes an iodine-containing ion-conducting additive to achieve fast charging capability of a solid-state lithium-sulfur battery. The iodine-containing ion-conducting additive contains an I element with redox activity, which can act as a redox mediator to promote the oxidation of Li2S. During fast charging, the I in the iodine-containing ion-conducting additive is - It can be electrochemically oxidized to oxidized iodine at the electrolyte | conductive material interface, and then the oxidized iodine will chemically oxidize the Li2S in contact with it. The reaction of oxidized iodine and Li2S has ultra-fast reaction kinetics, and the two can undergo a relatively fast chemical reaction when they are in physical contact. Therefore, the redox of iodine in the iodine-containing ion-conducting additive greatly improves the reaction kinetics of Li2S in the sulfur positive electrode. Moreover, this redox-mediated process based on the surface of the iodine-containing ion-conducting additive allows the solid-state conversion reaction of sulfur to proceed at the two-phase boundary of the iodine-containing ion-conducting additive | Li2S (this boundary is usually inactive in other solid-state lithium-sulfur batteries), and the contact range of the two-phase boundary is larger than that of the three-phase boundary of the iodine-containing ion-conducting additive | Li2S | conductive material. Through this redox-mediated strategy, the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery prepared therefrom have excellent fast charging performance.

[0086] Furthermore, the use of iodine-containing ion-conducting additives can achieve high cycle stability of solid-state lithium-sulfur batteries. The reversible redox reaction of the iodine-containing ion-conducting additives avoids the continuous degradation of the iodine-containing ion-conducting additives, so that the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery prepared therefrom have excellent cycle stability.

[0087] The "redox" mechanism discovered for the first time in the present invention is used to prepare solid-state lithium-sulfur battery sulfur positive electrode and solid-state lithium-sulfur battery, which have excellent rate performance and stability.

[0088] In some specific embodiments, the iodine-containing ion-conducting additive includes at least one compound of formula (1), formula (2), formula (3), formula (4), formula (5), formula (6) and formula (7):

[0089] Formula (1): Li 2+y+z B 2x S 1+3x I y X z(i.e., Li2S-xB2S3-yLiI-zLiX), where 0.15 ≤ x ≤ 4, 0 < y ≤ 2, 0 ≤ z ≤ 2, 0.05 ≤ y + z ≤ 2, and X includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN, such as two, three, four, or more. Among them, x includes, but is not limited to, any point value of 0.15, 0.2, 0.25, 0.3, 0.4, 0.5, 0.6, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. z includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. y + z includes, but is not limited to, any point value of 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.)

[0090] Formula (2): Li 2+y P 2d S 1+5d I y (i.e., Li2S-dP2S5-yLiI), where 0.2 ≤ d ≤ 0.5, 0 < y ≤ 2. Among them, d includes, but is not limited to, any point value of 0.2, 0.23, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.43, 0.45, 0.47, 0.5 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.)

[0091] Formula (3): Li 2+y P 2e Q 2f S 1+5e+5f I y , where 0.2 ≤ e ≤ 0.5, 0 < f ≤ 0.3, 0 < y ≤ 2, Q includes at least one of the elements As, Sb, and Bi, such as two or three. Among them, e includes, but is not limited to, any point value of 0.2, 0.23, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.43, 0.45, 0.47, 0.5 or the range value between any two of them. f includes, but is not limited to, any point value of 0.01, 0.03, 0.05, 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0092] Formula (4): Li 2+y P 2s Z g S 1+5s+2g I y , where 0.2 ≤ s ≤ 0.5, 0 < g ≤ 0.15, 0 < y ≤ 2, Z includes at least one of the elements Si, Ge, and Sn, such as two or three. Among them, s includes, but is not limited to, any point value of 0.2, 0.23, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.43, 0.45, 0.47, 0.5 or the range value between any two of them. g includes, but is not limited to, any point value of 0.01, 0.03, 0.05, 0.1, 0.13, 0.15 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0093] Formula (5): Li 2+y+c B 2bM 2a S 1+3b+5a I y A c , wherein, 0.15 ≤ b ≤ 3, 0.05 ≤ a ≤ 3, 0.25 ≤ b + a ≤ 4, 0 < y ≤ 2, 0 ≤ c ≤ 2, 0 ≤ y + c ≤ 2, M includes at least one of P, As, Sb and Bi, such as two, three, four or more; A includes at least one of F, Cl, Br, BH4, CN, OCN and SCN, such as two, three, four or more. Among them, b includes, but is not limited to, any point value of 0.15, 0.2, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.8, 3 or the range value between any two of them. a includes, but is not limited to, any point value of 0.05, 0.1, 0.15, 0.2, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.8, 3 or the range value between any two of them. b + a includes, but is not limited to, any point value of 0.25, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. c includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. y + c includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0094] Formula (6): Li 6-h PS 5-h Cl 1+h-y I y, where \(0\leq h\leq2\), \(0 < y\leq2\), and \(1 + h - y\geq0\); where \(h\) includes, but is not limited to, the point value of any one of \(0\), \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.18\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range value between any two of them. \(y\) includes, but is not limited to, the point value of any one of \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.18\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range value between any two of them. \(1 + h - y\) includes, but is not limited to, the point value of any one of \(0\), \(0.001\), \(0.005\), \(0.01\), \(0.03\), \(0.05\), \(0.08\), \(0.1\), \(0.3\), \(0.5\), \(0.8\), \(1\), \(1.5\), \(2\), \(2.5\) or the range value between any two of them.

[0095] Formula (7): Li 6-m PS 5-m Cl 1+m-n-y Br n I y, where \(0\leq m\leq2\), \(0\leq n\leq2\), \(0 < y\leq2\), and \(1 + m - n - y\geq0\). Here, \(m\) includes, but is not limited to, the point values of any one of \(0\), \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.18\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range values between any two of them. \(n\) includes, but is not limited to, the point values of any one of \(0\), \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.18\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range values between any two of them. \(y\) includes, but is not limited to, the point values of any one of \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.18\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range values between any two of them. \(1 + m - n - y\) includes, but is not limited to, the point values of any one of \(0\), \(0.001\), \(0.005\), \(0.01\), \(0.03\), \(0.05\), \(0.08\), \(0.1\), \(0.3\), \(0.5\), \(0.8\), \(1\), \(1.5\), \(2\), \(2.5\) or the range values between any two of them.

[0096] It can be understood that the \(y\) values in the above formulas (1), (2), (3), (4), (5), (6) and (7) can be the same or different.

[0097] In some specific embodiments, to further improve the fast charging ability and cycling performance of the sulfur cathode of the solid-state lithium-sulfur battery and the solid-state lithium-sulfur battery prepared therefrom, in the formula (1), \(0.25\leq x\leq2\), \(0.01\leq y\leq2\), \(0.01\leq y + z\leq2\).

[0098] In some specific embodiments, to further improve the fast charging ability and cycling performance of the sulfur cathode of the solid-state lithium-sulfur battery and the solid-state lithium-sulfur battery prepared therefrom, in the formula (2), \(0.25\leq d\leq0.5\), \(0.01\leq y\leq2\).

[0099] In some specific embodiments, in order to further improve the fast charging capability and cycle performance of the solid-state lithium-sulfur battery sulfur positive electrode and the solid-state lithium-sulfur battery prepared therefrom, in the formula (3), 0.25≤e≤0.5, 0 <f≤0.25,0.01<y≤2。

[0100] In some specific embodiments, in order to further improve the fast charging capability and cycle performance of the solid-state lithium-sulfur battery sulfur positive electrode and the solid-state lithium-sulfur battery prepared therefrom, in the formula (4), 0.25≤s≤0.5, 0 <g≤0.125,0.01<y≤2。

[0101] In some specific embodiments, in order to further improve the fast charging capability and cycle performance of the solid-state lithium-sulfur battery sulfur positive electrode and the solid-state lithium-sulfur battery prepared therefrom, in the formula (5), 0.25≤b≤2, 0.05≤a≤2, 0.3≤b+a≤3, 0.01≤y≤2, 0.01≤y+c≤2.

[0102] In some specific embodiments, in order to further improve the fast charging capability and cycle performance of the solid-state lithium-sulfur battery sulfur positive electrode and the solid-state lithium-sulfur battery prepared therefrom, in the formula (5), 0.25≤b≤1.5, 0.05≤a≤1, 0.3≤b+a≤2.5, 0.01≤y≤2, 0≤c≤2, 0.01≤y+c≤2.

[0103] In some specific embodiments, in order to further improve the fast charging capability and cycle performance of the solid-state lithium-sulfur battery sulfur positive electrode and the solid-state lithium-sulfur battery prepared therefrom, in the formula (6), 0≤h≤1, 0.01≤y≤2, 1+hy>0.

[0104] In some specific embodiments, in order to further improve the fast charging capability and cycle performance of the solid-state lithium-sulfur battery sulfur positive electrode and the solid-state lithium-sulfur battery prepared therefrom, in the formula (7), 0≤m≤1, 0≤n≤1, 0.01≤y≤2, 1+mny>0.

[0105] In some specific embodiments, the solid-state lithium-sulfur battery sulfur positive electrode also includes a sulfur-containing active material, and the sulfur-containing active material includes at least one of a sulfur element, a sulfur-selenium alloy, a composite material of sulfur and a carbon material, a composite material of sulfur and a metal sulfide, Li2S, a composite material of Li2S and a carbon material, a composite material of Li2S and LiI, and a composite material of Li2S and a metal sulfide.

[0106] In some specific embodiments, the carbon material includes at least one of Ketjen black, conductive carbon black, vapor grown carbon fiber reinforcement (VGCF), carbon nanotubes, mesoporous carbon, microporous carbon, graphene and acetylene black, but is not limited thereto.

[0107] In some specific embodiments, the metal sulfide includes at least one of iron sulfide, ferrous sulfide, titanium sulfide, nickel sulfide, cobalt sulfide, copper sulfide, zinc sulfide, manganese sulfide, and chromium sulfide, but is not limited thereto.

[0108] In some specific embodiments, the solid-state lithium-sulfur battery sulfur positive electrode further includes a conductive carbon additive.

[0109] In some specific embodiments, the conductive carbon additive includes but is not limited to one or more of Ketjen black, conductive carbon black, vapor grown carbon fiber reinforcement (VGCF), carbon nanotubes, mesoporous carbon, microporous carbon, graphene and acetylene black.

[0110] It is understandable that when the sulfur-containing active material contains carbon material or other conductive materials, the above-mentioned conductive carbon additive may not be additionally added to the sulfur positive electrode of the solid-state lithium-sulfur battery.

[0111] In some specific embodiments, in order to further improve the capacity of the sulfur positive electrode of the solid-state lithium-sulfur battery and the fast charging ability and cycle performance of the solid-state lithium-sulfur battery prepared therefrom, the mass ratio of the sulfur-containing active material, the iodine-containing ion-conducting additive and the conductive carbon additive is 30-95 (for example, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85 or 90): 5-70 (for example, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60 or 65): 0-50 (for example, 5, 10, 15, 20, 25, 30, 35, 40 or 45). Among them, too small a proportion of the sulfur-containing active material will result in too small an overall specific capacity of the sulfur positive electrode, and too high a proportion will result in too low electronic conductivity and ionic conductivity of the electrode, thereby limiting the overall capacity of the sulfur positive electrode. If the proportion of iodine-containing ion-conducting additive is too small, the redox mediation effect of the sulfur cathode will not be obvious enough and / or the ion conductivity of the electrode will be insufficient; if the proportion is too high, the sulfur cathode will have too little sulfur-containing active material, and the overall specific capacity of the sulfur cathode will be too low. If the proportion of conductive carbon additive is too high, the overall specific capacity of the sulfur cathode will be too small.

[0112] In a second aspect, the present invention provides a positive electrode material for a solid-state lithium-sulfur battery, wherein the positive electrode material comprises an iodine-containing ion-conducting additive, wherein the iodine-containing ion-conducting additive contains at least iodine, lithium and sulfur, and the molar amount of iodine per mole of the iodine-containing ion-conducting additive is n I is 0 <n I ≤2, the iodine-containing ion-conducting additive comprises at least one compound of formula (1), formula (2), formula (3), formula (4), formula (5), formula (6) and formula (7).

[0113] Formula (1): Li 2+y+z B 2x S 1+3xI y X z , where 0.15 ≤ x ≤ 4, 0 < y ≤ 2, 0 ≤ z ≤ 2, 0.05 ≤ y + z ≤ 2, and X includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN, such as two, three, four, five, or more. Among them, x includes, but is not limited to, any point value of 0.15, 0.2, 0.25, 0.3, 0.4, 0.5, 0.6, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. z includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. y + z includes, but is not limited to, any point value of 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0114] Formula (2): Li 2+y P 2d S 1+5d I y , where 0.2 ≤ d ≤ 0.5, 0 < y ≤ 2. Among them, d includes, but is not limited to, any point value of 0.2, 0.23, 0.25, 0.28, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0115] Formula (3): Li 2+y P 2e Q 2f S 1+5e+5f I y , where 0.2 ≤ e ≤ 0.5, 0 < f ≤ 0.3, 0 < y ≤ 2, Q includes at least one of the elements As, Sb, and Bi, such as two or three. Among them, e includes, but is not limited to, any point value of 0.2, 0.23, 0.25, 0.28, 0.3, 0.32, 0.35, 0.37, 0.4, 0.43, 0.45, 0.48, 0.5 or the range value between any two of them. f includes, but is not limited to, any point value of 0.01, 0.03, 0.05, 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0116] Formula (4): Li 2+y P 2s Z g S 1+5s+2g I y , where 0.2 ≤ s ≤ 0.5, 0 < g ≤ 0.15, 0 < y ≤ 2, Z includes at least one of the elements Si, Ge, and Sn, such as two or three. Among them, s includes, but is not limited to, any point value of 0.2, 0.23, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.47, 0.5 or the range value between any two of them. g includes, but is not limited to, any point value of 0.01, 0.03, 0.05, 0.1, 0.13, 0.15 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0117] Formula (5): Li 2+y+c B 2b M2a S 1+3b+5a I y A c , where 0.15 ≤ b ≤ 3, 0.05 ≤ a ≤ 3, 0.25 ≤ b + a ≤ 4, 0 < y ≤ 2, 0 ≤ c ≤ 2, 0 ≤ y + c ≤ 2, M includes at least one of P, As, Sb, and Bi, such as two, three, four, or more; A includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN, such as two, three, four, or more. Among them, b includes, but is not limited to, any point value of 0.15, 0.2, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.8, 3 or the range value between any two of them. a includes, but is not limited to, any point value of 0.05, 0.1, 0.15, 0.2, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.7, 3 or the range value between any two of them. b + a includes, but is not limited to, any point value of 0.25, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 or the range value between any two of them. y includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.17, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. c includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them. y + c includes, but is not limited to, any point value of 0.001, 0.003, 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.13, 0.16, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or the range value between any two of them.

[0118] Formula (6): Li 6-h PS 5-h Cl 1+h-y I y, where \(0\leq h\leq2\), \(0 < y\leq2\), and \(1 + h - y\geq0\); where \(h\) includes, but is not limited to, the point value of any one of \(0\), \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.17\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range value between any two of them. \(y\) includes, but is not limited to, the point value of any one of \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.18\), \(0.2\), \(0.4\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range value between any two of them. \(1 + h - y\) includes, but is not limited to, the point value of any one of \(0\), \(0.001\), \(0.005\), \(0.01\), \(0.03\), \(0.05\), \(0.08\), \(0.1\), \(0.3\), \(0.5\), \(0.8\), \(1\), \(1.5\), \(2\), \(2.5\) or the range value between any two of them.

[0119] Formula (7): Li 6-m PS 5-m Cl 1+m-n-y Br n I y, where \(0\leq m\leq2\), \(0\leq n\leq2\), \(0 < y\leq2\), and \(1 + m - n - y\geq0\). Here, \(m\) includes, but is not limited to, the point value of any one of \(0\), \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.17\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range value between any two of them. \(n\) includes, but is not limited to, the point value of any one of \(0\), \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.15\), \(0.17\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range value between any two of them. \(y\) includes, but is not limited to, the point value of any one of \(0.001\), \(0.003\), \(0.005\), \(0.01\), \(0.02\), \(0.03\), \(0.05\), \(0.06\), \(0.08\), \(0.1\), \(0.13\), \(0.16\), \(0.18\), \(0.2\), \(0.3\), \(0.5\), \(0.6\), \(0.8\), \(1\), \(1.1\), \(1.2\), \(1.3\), \(1.4\), \(1.5\), \(1.6\), \(1.7\), \(1.8\), \(1.9\), \(2\) or the range value between any two of them. \(1 + m - n - y\) includes, but is not limited to, the point value of any one of \(0\), \(0.001\), \(0.005\), \(0.01\), \(0.03\), \(0.05\), \(0.08\), \(0.1\), \(0.3\), \(0.5\), \(0.8\), \(1\), \(1.5\), \(2\), \(2.5\) or the range value between any two of them.

[0120] It can be understood that the \(y\) values in the above formulas (1), (2), (3), (4), (5), (6) and (7) can be the same or different.

[0121] The cathode material for solid-state lithium-sulfur batteries provided by the present invention can achieve the fast charging ability and cycle stability of solid-state lithium-sulfur batteries by introducing a specific type of iodine-containing ion-conducting additive. Specifically, the iodine-containing ion-conducting additive contains redox-active I element, which can act as a redox mediator to promote the oxidation of Li2S. During fast charging, I in the iodine-containing ion-conducting additive -It can be electrochemically oxidized to oxidized iodine at the electrolyte | conductive material interface, and then the oxidized iodine will chemically oxidize the Li2S in contact with it. The reaction of oxidized iodine and Li2S has ultra-fast reaction kinetics, and the two can undergo a relatively fast chemical reaction when they are in physical contact. Therefore, the redox of iodine in the iodine-containing ion-conducting additive greatly improves the reaction kinetics of Li2S in the sulfur positive electrode. Moreover, this redox-mediated process based on the surface of the iodine-containing ion-conducting additive allows the solid-state conversion reaction of sulfur to proceed at the two-phase boundary of the iodine-containing ion-conducting additive | Li2S (this boundary is usually inactive in other solid-state lithium-sulfur batteries), and the contact range of the two-phase boundary is larger than that of the three-phase boundary of the iodine-containing ion-conducting additive | Li2S | conductive material. Through this redox-mediated strategy, the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery prepared therefrom have excellent fast charging performance.

[0122] At the same time, the introduction of iodine-containing ion-conducting additives can achieve high cycle stability of solid-state lithium-sulfur batteries. Specifically, the reversible redox reaction of the iodine-containing ion-conducting additives avoids the continuous degradation of the iodine-containing ion-conducting additives, so that the sulfur positive electrode of the solid-state lithium-sulfur battery and the battery prepared therefrom have excellent cycle stability.

[0123] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for the solid-state lithium-sulfur battery and the solid-state lithium-sulfur battery prepared therefrom, in the above formula (1), 0.25≤x≤2, 0.01≤y≤2, 0.01≤y+z≤2.

[0124] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for solid-state lithium-sulfur batteries and the solid-state lithium-sulfur batteries prepared therefrom, in the above formula (2), 0.25≤d≤0.5, 0.01≤y≤2.

[0125] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for solid-state lithium-sulfur batteries and the solid-state lithium-sulfur batteries prepared therefrom, in the above formula (3), 0.25≤e≤0.5, 0 <f≤0.25,0.01<y≤2。

[0126] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for solid-state lithium-sulfur batteries and the solid-state lithium-sulfur batteries prepared therefrom, in the above formula (4), 0.25≤s≤0.5, 0 <g≤0.125,0.01<y≤2。

[0127] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for the solid-state lithium-sulfur battery and the solid-state lithium-sulfur battery prepared therefrom, in the above formula (5), 0.25≤b≤2, 0.05≤a≤2, 0.3≤b+a≤3, 0.01≤y≤2, 0.01≤y+c≤2.

[0128] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for the solid-state lithium-sulfur battery and the solid-state lithium-sulfur battery prepared therefrom, in the above formula (5), 0.25≤b≤1.5, 0.05≤a≤1, 0.3≤b+a≤2.5, 0.01≤y≤2, 0≤c≤2, 0.01≤y+c≤2.

[0129] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for solid-state lithium-sulfur batteries and the solid-state lithium-sulfur batteries prepared therefrom, in the above formula (6), 0≤h≤1, 0.01≤y≤2, 1+hy>0.

[0130] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for solid-state lithium-sulfur batteries and the solid-state lithium-sulfur batteries prepared therefrom, in the above formula (7), 0≤m≤1, 0≤n≤1, 0.01≤y≤2, 1+mny>0.

[0131] In some specific embodiments, the positive electrode material further includes a sulfur-containing active material.

[0132] In some specific embodiments, the sulfur-containing active material includes at least one of elemental sulfur, sulfur-selenium alloy, a composite material of sulfur and carbon material, a composite material of sulfur and metal sulfide, Li2S, a composite material of Li2S and carbon material, a composite material of Li2S and LiI, and a composite material of Li2S and metal sulfide.

[0133] The carbon material includes but is not limited to at least one of Ketjen black, conductive carbon black, vapor grown carbon fiber reinforcement (VGCF), carbon nanotubes, mesoporous carbon, microporous carbon, graphene and acetylene black.

[0134] The metal sulfide includes, but is not limited to, at least one of iron sulfide, ferrous sulfide, titanium sulfide, nickel sulfide, cobalt sulfide, copper sulfide, zinc sulfide, manganese sulfide, and chromium sulfide.

[0135] In some specific embodiments, the positive electrode material further includes a conductive carbon additive.

[0136] In some specific embodiments, in order to further improve the fast charging capability and cycle stability of the positive electrode material for solid-state lithium-sulfur batteries and the solid-state lithium-sulfur batteries prepared therefrom, the mass ratio of the sulfur-containing active material, the conductive carbon additive and the iodine-containing ion-conducting additive is 30-95 (e.g., 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85 or 90): 0-50 (e.g., 5, 10, 15, 20, 25, 30, 35, 40 or 45): 5-70 (e.g., 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60 or 65).

[0137] In some specific embodiments, the conductive carbon additive includes at least one of Ketjen black, conductive carbon black, vapor-grown carbon fiber reinforcement, carbon nanotubes, mesoporous carbon, microporous carbon, graphene and acetylene black.

[0138] It is understandable that when the sulfur-containing active material contains carbon material or other conductive materials, the above-mentioned conductive carbon additive may not be additionally added to the sulfur positive electrode of the solid-state lithium-sulfur battery.

[0139] In a third aspect, the present invention provides a method for preparing the positive electrode material for a solid-state lithium-sulfur battery, comprising the following steps:

[0140] The iodine-containing ion-conducting additive and the sulfur-containing active material are uniformly mixed to obtain the positive electrode material for the solid-state lithium-sulfur battery.

[0141] Alternatively, the iodine-containing ion-conducting additive is uniformly mixed with the sulfur-containing active material and the conductive carbon additive to obtain the positive electrode material for the solid-state lithium-sulfur battery.

[0142] The method for preparing the positive electrode material for a solid-state lithium-sulfur battery provided by the present invention has the advantages of simple operation, short process, low cost and suitability for mass production.

[0143] Moreover, by adding iodine-containing ion-conducting additives, the prepared positive electrode material has high rate performance, fast charging capability and excellent cycle stability.

[0144] In some specific embodiments, the mixing method includes at least one of grinding, ball milling, vibration milling and high-speed stirring. The rotation speed of the ball milling can be 50 to 500 rpm, and the time of the ball milling can be 0.1 to 20 hours, but is not limited thereto.

[0145] In some specific embodiments, the method for preparing the sulfur-containing active material includes: mixing the raw materials and then heating them, wherein the mixing method can be, for example, hand grinding, ball grinding, vibration grinding and high-speed stirring, and the heating temperature can be, for example, kept at 100 to 300° C. for 10 to 20 hours, and the heating can be carried out in a sealed vacuum quartz tube; the atmosphere for the mixing and heating can be an inert atmosphere, but is not limited thereto.

[0146] In a fourth aspect, the present invention provides a fast-chargeable solid-state lithium-sulfur battery, comprising the positive electrode material for a solid-state lithium-sulfur battery.

[0147] The solid-state lithium-sulfur battery containing the positive electrode material for the solid-state lithium-sulfur battery has fast charging capability, high cycle stability and high energy density.

[0148] Furthermore, the fast-chargeable solid-state lithium-sulfur battery provided by the present invention uses sulfur, a low-cost raw material with extremely abundant reserves on Earth, and the manufacturing cost of the battery is much lower than that of existing commercial lithium-ion batteries.

[0149] In some specific embodiments, the solid-state lithium-sulfur battery further includes a solid electrolyte separator and a negative electrode.

[0150] In some specific embodiments, the solid-state lithium-sulfur battery may be in the form of a mold battery, a button battery, a soft-pack battery, a square-shell battery, and a cylindrical battery.

[0151] In some specific embodiments, the negative electrode includes at least one of lithium metal, lithium alloy, graphite, silicon, silicon-carbon composite material, silicon oxide and lithium-carbon material (referring to a composite material of lithium metal and carbon), but is not limited thereto.

[0152] In some specific embodiments, the lithium alloy includes but is not limited to at least one of a lithium indium alloy, a lithium magnesium alloy, a lithium aluminum alloy, a lithium boron alloy, a lithium tin alloy and a lithium silicon alloy.

[0153] In some specific embodiments, the solid electrolyte separator includes but is not limited to at least one of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte, a polymer electrolyte, a sulfide-polymer composite electrolyte, a halide-polymer composite electrolyte and an oxide-polymer composite electrolyte.

[0154] In some specific embodiments, the positive electrode material for solid-state lithium-sulfur battery is used to make a sulfur positive electrode, and the sulfur loading capacity of the sulfur positive electrode is 0.5 to 20 mg·cm -2 , including but not limited to 1 mg cm -2 , 2mg·cm -2 , 3mg·cm -2 , 4mg·cm -2 , 5mg·cm-2 , 6mg·cm -2 , 8mg·cm -2 、10mg·cm -2 , 12mg·cm -2 、15mg·cm -2 、18mg·cm -2 The sulfur loading in the present invention refers to the content of active sulfur substances in the sulfur-containing active material in the sulfur positive electrode, such as sulfur and Li2S. The positive electrode material provided by the present invention can be used to prepare a sulfur positive electrode with a high surface loading, which can effectively improve the overall energy density of a solid-state lithium-sulfur battery.

[0155] In some specific embodiments, the solid-state lithium-sulfur battery sulfur positive electrode containing the iodine-conducting ion additive and / or the solid-state lithium-sulfur battery containing the positive electrode material for the solid-state lithium-sulfur battery: the specific capacity at a charging rate of 10C is ≥1200mAh·g -1 , specific capacity at 20C charging rate ≥ 1100mAh·g -1 , specific capacity at 50C charging rate ≥750mAh·g -1 , specific capacity at 100C charging rate ≥500mAh·g -1 , specific capacity at 150C charging rate ≥ 400mAh g -1 (60°C). Specific capacity (mAh·g -1 ) are calculated based on the mass of active sulfur substances in the sulfur-containing active materials in the sulfur positive electrode, such as sulfur and Li2S.

[0156] In some specific embodiments, the solid-state lithium-sulfur battery sulfur positive electrode containing the iodine-conducting ion additive and / or the solid-state lithium-sulfur battery containing the positive electrode material for the solid-state lithium-sulfur battery: the capacity retention rate after 25,000 cycles at 5C is ≥75%.

[0157] Taking the LiIn alloy negative electrode as an example, the assembly of an all-solid-state lithium-sulfur battery in a mold battery includes the following steps: First, 70 to 150 mg of solid electrolyte powder is placed in a PEEK (polyetheretherketone) cylinder, and both ends are pressed with Ti rods at a pressure of 100 to 150 MPa for 0.5 to 3 minutes to form a solid electrolyte layer (i.e., a solid electrolyte diaphragm). Then, the positive electrode material for the solid-state lithium-sulfur battery is evenly spread on top of the solid electrolyte layer and pressed at a pressure of 300 to 350 MPa for 2 to 5 minutes. Indium foil and lithium foil are attached to the other side of the solid electrolyte layer. Then, the mold battery is placed in a stainless steel casing and a pressure of 20 to 70 MPa is applied.

[0158] In a fifth aspect, the present invention provides an electrical device comprising the solid-state lithium-sulfur battery.

[0159] The solid-state lithium-sulfur battery has excellent fast charging performance and long cycle stability, and can be used in electrical equipment, such as electric vehicles, renewable energy storage, portable electronic devices, aerospace and other fields, which are not limited by the present invention.

[0160] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0161] Example 1

[0162] The method for preparing the positive electrode material for a solid-state lithium-sulfur battery provided in this embodiment comprises the following steps:

[0163] Li2S, B2S3, LiI, and P2S5 were weighed in a molar ratio of 30:25:45:5, fully melted at 800°C for 20 hours, taken out, quickly placed in an ice-water mixture for cooling and quenching, and then hand-ground into powder to obtain the iodine-containing ion-conducting additive Li 3.5 B 1.67 P 0.33 S 4.33 I 1.5 (LBPSI). That is, the molar amount of iodine in each mole of iodine-containing ion-conducting additive n I =1.5.

[0164] Sulfur element (S) and Ketjen black (KB for short) were weighed in a mass ratio of 75:25, ground and placed in a quartz tube and sealed under vacuum. The tube was then placed in a muffle furnace and heated to 155°C at a heating rate of 1°C / min and kept warm for 10 hours to obtain a sulfur-containing active material.

[0165] The above sulfur-containing active material, the above iodine-containing ion-conducting additive and the conductive carbon black Super P (conductive carbon additive, abbreviated as SP) are weighed in a mass ratio of 4:5:1 and placed in a zirconia ball mill, and the mass ratio of zirconia beads to the ball-milled material is 40:1. The ball mill is packaged in an inert atmosphere. The ball mill is placed in a planetary ball mill, and the positive electrode materials are mixed evenly at a rotation speed of 500 rpm and a rotation time of 20 hours to obtain a positive electrode material for a solid-state lithium-sulfur battery.

[0166] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment comprises the following steps: in an inert atmosphere, 80 mg of Li 3.5 B 1.67 P 0.33 S4.33 I 1.5 The solid electrolyte membrane layer was formed by placing it in a PEEK cylinder with a diameter of 10 mm and pressing it with customized Ti columns at both ends at a pressure of 128 MPa for 1 min. 3.5 B 1.67 P 0.33 S 4.33 I 1.5 Then, the sulfur loading was 1.1 mg cm -2 The positive electrode material for solid-state lithium-sulfur batteries prepared above was evenly spread on the top of the solid electrolyte layer (based on sulfur) and pressed at a pressure of 320 MPa for 3 minutes. On the other side of the solid electrolyte layer, a thin layer of indium foil (9 mm in diameter) and a thin lithium foil (7 mm in diameter) were attached. After that, the mold battery was placed in a customized stainless steel casing and a pressure of 64 MPa was applied to obtain an all-solid-state lithium-sulfur battery.

[0167] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested by placing the battery in an oven at 25°C and performing a constant current charge and discharge test on a NEWARE battery test system. Figure 1 and Figure 2 As shown, at 25°C and a fixed charge and discharge rate of 5C, the battery has a capacity of 823 mAh g -1 The specific capacity of the battery is 80.2% after 25,000 cycles, showing extremely high stability.

[0168] This shows that the prepared solid-state lithium-sulfur battery sulfur positive electrode and its battery not only have a high specific capacity, but also have excellent cycle stability.

[0169] Example 2

[0170] The positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment is the same as that in Example 1; the preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that the sulfur loading in the positive electrode is 1.05 mg·cm -2 (calculated as elemental sulfur).

[0171] The performance test of the all-solid-state lithium-sulfur battery prepared in this embodiment was carried out: the all-solid-state lithium-sulfur battery was placed in an oven at 60°C and a constant current charge and discharge test was carried out on a NEWARE battery test system. The test results are shown in FIG. Figure 3 and Figure 4 As shown in Figure 2, at 60°C, at a fixed discharge rate of 2C and charge rates of 10C, 20C, and 50C, the corresponding specific capacities are 1361 mAh g -1 , 1162mAh·g -1 and 815mAh·g -1Even at 100C and 150C charging rates, the battery still has 594mAh·g -1 and 432mAh·g -1 The specific capacity shows super fast charging performance.

[0172] This indicates that the iodine-containing ion-conducting additive acts as a redox mediator to promote the oxidation of Li2S. - The interface between the iodine-containing ion-conducting additive and the conductive material in the sulfur positive electrode is electrochemically oxidized into oxidized iodine, and then the oxidized iodine chemically oxidizes the Li2S in contact with it. The redox mediated process on the surface of the iodine-containing ion-conducting additive allows the reaction at the iodine-containing ion-conducting additive|Li2S two-phase interface to proceed, thereby improving the solid-state reaction kinetics of sulfur.

[0173] Example 3

[0174] The preparation method of the positive electrode material for a solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that the mass ratio of the sulfur-containing active material, the iodine-containing ion-conducting additive and the conductive carbon black Super P is replaced with 6:3.5:0.5.

[0175] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that the sulfur loading in the positive electrode is 1.9 mg·cm -2 .

[0176] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested by placing the battery in an oven at 25°C and performing a constant current charge and discharge test on a NEWARE battery test system. Figure 5 and Figure 6 As shown in the figure, at 25℃ and a fixed charge and discharge rate of 0.2C, the battery has a capacity of 1049mAh·g -1 The specific capacity can be stably cycled for 200 cycles with almost no capacity decay. Therefore, the all-solid-state lithium-sulfur battery with a high sulfur content in the positive electrode also has a high specific capacity and cycle stability.

[0177] Example 4

[0178] The positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment is the same as that in Example 1; the preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that the sulfur loading in the positive electrode is 6.3 mg·cm -2 .

[0179] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested by placing the battery in an oven at 25°C and performing a constant current charge and discharge test on a NEWARE battery test system. Figure 7 and Figure 8 As shown, at 25°C and a fixed charge and discharge rate of 0.1C, the battery has a capacity of 1413 mAh g -1 The specific capacity of the battery is 85.3% after 100 cycles. Therefore, the battery with high sulfur loading positive electrode still shows high specific capacity and cycle stability.

[0180] Example 5

[0181] The positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment is the same as that in Example 1; the preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that the sulfur loading in the positive electrode is 1.0 mg·cm -2 .

[0182] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested by placing the battery in an oven at 60°C and performing a constant current charge and discharge test on a NEWARE battery test system. Fig. 9 and Fig.10 As shown in Figure 2, at 60°C and a fixed charge and discharge rate of 15C, the specific capacity of the battery after 1000 cycles is 1110 mAh g -1 After 10,000 cycles, it still has 979 mAh g -1 Therefore, at 60°C and high rate (15C), the battery still exhibits extremely high specific capacity and cycle stability.

[0183] Example 6

[0184] The preparation method of the positive electrode material for solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in embodiment 1, except that the iodine-containing ion-conducting additive and the preparation method thereof are different. The iodine-containing ion-conducting additive Li 2.29 P 0.66 S 2.65 I 0.29 The preparation method is as follows: Li2S, P2S5, and LiI are weighed according to the molar ratio of the target chemical formula, mechanically ball-milled and mixed, sintered at 250°C, and then ground into powder to obtain the iodine-containing ion-conducting additive Li 2.29 P 0.66 S 2.65 I 0.29 That is, the molar amount of iodine in each mole of iodine-containing ion-conducting additive n I =0.29.

[0185] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment has a sulfur loading of 1.0 mg·cm -2In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li 5.5 PS 4.5 Cl 1.5 .

[0186] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested by placing the battery in an oven at 25°C and performing a constant current charge and discharge test on a NEWARE battery test system. Fig.11 and Fig.12 As shown in Figure 2, at 25°C, at a fixed discharge rate of 1C and a charge rate of 2C and 10C, the specific capacity is 1300 mAh g -1 and 660mAh·g -1 .

[0187] Example 7

[0188] The preparation method of the positive electrode material for solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in embodiment 1, except that the iodine-containing ion-conducting additive and the preparation method thereof are different. 3.5 B 1.67 S 3.5 I 1.5 The preparation method is as follows: Li2S, B2S3, and LiI are weighed in a molar ratio of 30:25:45, fully melted at 800°C for 10 hours, taken out, quickly cooled and quenched in an ice-water mixture, and then hand-ground into powder to obtain the iodine-containing ion-conducting additive Li 3.5 B 1.67 S 3.5 I 1.5 That is, the molar amount of iodine in each mole of iodine-containing ion-conducting additive n I =1.5.

[0189] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment has a sulfur loading of 1.0 mg·cm -2 In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li 5.5 PS 4.5 Cl 1.5 .

[0190] The performance test of the all-solid-state lithium-sulfur battery prepared in this embodiment is as follows: at 25°C, at a discharge rate of 1C and a charge rate of 10C, the battery specific capacity is 680 mAh g -1 .

[0191] Example 8

[0192] The preparation method of the positive electrode material for solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in embodiment 1, except that the iodine-containing ion-conducting additive and the preparation method thereof are different. 2.29 P 0.66 As 0.1 S 2.9 I 0.29 The preparation method is as follows: Li2S, P2S5, LiI, As2S5 are prepared according to the target chemical formula Li 2.29 P 0.66 As 0.1 S 2.9 I 0.29 The molar ratio is weighed, mechanically ball-milled and mixed, sintered at 250 ° C, and then ground into powder to obtain the iodine-containing ion-conducting additive Li 2.29 P 0.66 As 0.1 S 2.9 I 0.29 That is, the molar amount of iodine in each mole of iodine-containing ion-conducting additive n I =0.29.

[0193] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment has a sulfur loading of 1.15 mg·cm -2 In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li 5.5 PS 4.5 Cl 1.5 .

[0194] The performance test of the all-solid-state lithium-sulfur battery prepared in this embodiment is as follows: at 25°C, at a discharge rate of 1C and a charge rate of 10C, the battery specific capacity is 625 mAh g -1 .

[0195] Example 9

[0196] The preparation method of the positive electrode material for solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in embodiment 1, except that the iodine-containing ion-conducting additive and the preparation method thereof are different. 2.29 P 0.66 Si 0.05 S 2.75 I 0.29 The preparation method is as follows: Li2S, P2S5, LiI, SiS2 are prepared according to the target chemical formula Li 2.29 P 0.66 Si 0.05 S 2.75 I 0.29The molar ratio is weighed, mechanically ball-milled and mixed, sintered at 250 ° C, and then ground into powder to obtain the iodine-containing ion-conducting additive Li 2.29 P 0.66 Si 0.05 S 2.75 I 0.29 That is, the molar amount of iodine in each mole of iodine-containing ion-conducting additive n I =0.29.

[0197] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment has a sulfur loading of 1.2 mg·cm -2 In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li 5.5 PS 4.5 Cl 1.5 .

[0198] The performance test of the all-solid-state lithium-sulfur battery prepared in this embodiment is as follows: at 25°C, at a discharge rate of 1C and a charge rate of 10C, the battery specific capacity is 565 mAh·g -1 .

[0199] Example 10

[0200] The preparation method of the positive electrode material for solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in embodiment 1, except that the iodine-containing ion-conducting additive and the preparation method thereof are different. 5.4 PS 4.4 Cl 0.8 I 0.8 The preparation method is as follows: Li2S, P2S5, LiI, LiCl are prepared according to the target chemical formula Li 5.4 PS 4.4 Cl 0.8 I 0.8 The molar ratio of the iodine-containing ion-conducting additive Li is weighed, mechanically ball-milled and mixed, sintered at 550°C, and then ground into powder to obtain the iodine-containing ion-conducting additive Li 5.4 PS 4.4 Cl 0.8 I 0.8 That is, the molar amount of iodine in each mole of iodine-containing ion-conducting additive n I =0.8.

[0201] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment has a sulfur loading of 1.15 mg·cm -2 In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li5.5 PS 4.5 Cl 1.5 .

[0202] The performance test of the all-solid-state lithium-sulfur battery prepared in this embodiment is as follows: at 25°C, at a discharge rate of 1C and a charge rate of 10C, the battery specific capacity is 640 mAh g -1 .

[0203] Embodiment 11

[0204] The preparation method of the positive electrode material for solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in embodiment 1, except that the iodine-containing ion-conducting additive and the preparation method thereof are different. 5.8 PS 4.8 Cl 0.6 Br 0.2 I 0.4 The preparation method is as follows: Li2S, P2S5, LiI, LiCl, LiBr are prepared according to the target chemical formula Li 5.8 PS 4.8 Cl 0.6 Br 0.2 I 0.4 The molar ratio of the iodine-containing ion-conducting additive Li is weighed, mechanically ball-milled and mixed, sintered at 550°C, and then ground into powder to obtain the iodine-containing ion-conducting additive Li 5.8 PS 4.8 Cl 0.6 Br 0.2 I 0.4 That is, the molar amount of iodine in each mole of iodine-containing ion-conducting additive n I =0.4.

[0205] The preparation method of the all-solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode material for the solid-state lithium-sulfur battery prepared in this embodiment has a sulfur loading of 1.15 mg·cm -2 In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li 5.5 PS 4.5 Cl 1.5 .

[0206] The performance test of the all-solid-state lithium-sulfur battery prepared in this embodiment is as follows: at 25°C, at a discharge rate of 1C and a charge rate of 10C, the battery specific capacity is 620 mAh g -1 .

[0207] Example 12

[0208] The preparation method of the positive electrode material for a solid-state lithium-sulfur battery provided in this embodiment is basically the same as that in Example 1, except that the mass ratio of the sulfur-containing active material, the iodine-containing ion-conducting additive and the conductive carbon black Super P is replaced with 6.7:2.3:1.

[0209] An all-solid-state lithium-sulfur battery was prepared by using the positive electrode material prepared in this embodiment and referring to the preparation method of the all-solid-state lithium-sulfur battery in Example 1.

[0210] The performance test of the all-solid-state lithium-sulfur battery prepared in this embodiment was carried out: the battery was placed in an oven at 30°C. At 30°C and a charge and discharge rate of 0.2C, the battery specific capacity was 890 mAh·g -1 .

[0211] Comparative Example 1

[0212] The preparation method of the positive electrode material for solid-state lithium-sulfur battery provided in this comparative example is basically the same as that in Example 1, except that the iodine-containing ion-conducting additive is replaced by Li 5.5 PS 4.5 Cl 1.5 The preparation method is as follows: Li2S, P2S5, and LiCl are weighed according to the target chemical formula, mechanically ball-milled and mixed, sintered at 500°C, and then ground into powder to obtain Li 5.5 PS 4.5 Cl 1.5 .

[0213] The preparation method of the all-solid-state lithium-sulfur battery provided in this comparative example is basically the same as that in Example 1, except that: the positive electrode material prepared in this comparative example has a sulfur loading of 1.05 mg·cm -2 In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li 5.5 PS 4.5 Cl 1.5 (easy to operate).

[0214] The performance of the all-solid-state lithium-sulfur battery prepared in this comparative example was tested by placing the battery in an oven at 60°C and performing a constant current charge and discharge test on a NEWARE battery test system. Fig.13 and Fig.14 As shown in Figure 2, at 60°C, at a fixed discharge rate of 2C and a charge rate of 50C, the specific capacity is only 123 mAh g -1 .

[0215] Comparative Example 2

[0216] The positive electrode material for solid-state lithium-sulfur battery prepared in Comparative Example 1 is used. The preparation method of the all-solid-state lithium-sulfur battery provided in this comparative example is basically the same as that in Comparative Example 1, except that the sulfur loading in the positive electrode is 1.1 mg·cm -2 .

[0217] The performance of the all-solid-state lithium-sulfur battery prepared in this comparative example was tested by placing the battery in an oven at 25°C and performing a constant current charge and discharge test on a NEWARE battery test system. Fig.15 and Fig.16 As shown in the figure, at 25°C and a fixed charge and discharge rate of 5C, the battery capacity quickly decays to 400mAh g -1 After 10,000 cycles, the battery capacity is only 81 mAh g -1 Specific capacity.

[0218] Comparative Example 3

[0219] The positive electrode material for solid-state lithium-sulfur battery prepared in Comparative Example 1 is used. The preparation method of the all-solid-state lithium-sulfur battery provided in this comparative example is basically the same as that in Comparative Example 1, except that the sulfur loading in the positive electrode is 1 mg·cm -2 .

[0220] The performance of the all-solid-state lithium-sulfur battery prepared in this comparative example was tested by placing the battery in an oven at 60°C and performing a constant current charge and discharge test on a NEWARE battery test system. Fig.17 and Fig.18 As shown, at 60°C and a fixed charge and discharge rate of 15C, the battery specific capacity decays very quickly, and the battery has almost no capacity after only a few hundred cycles, which means that the battery has serious side reactions.

[0221] Comparative Example 4

[0222] The preparation method of the positive electrode material for a solid-state lithium-sulfur battery provided in this comparative example is basically the same as that in Example 1, except that the iodine-containing ion-conducting additive is replaced by Li3PS4 that does not contain iodine element. The preparation method is as follows: Li2S and P2S5 are weighed according to the target chemical formula, mechanically ball-milled and mixed, sintered at 250°C, and then ground into powder to obtain Li3PS4.

[0223] The preparation method of the all-solid-state lithium-sulfur battery provided in this comparative example is basically the same as that in Example 1, except that: the positive electrode material prepared in this comparative example has a sulfur loading of 1 mg·cm -2 In addition, the solid electrolyte powder in the solid electrolyte separator layer is replaced with Li 5.5 PS 4.5 Cl 1.5 .

[0224] The performance of the all-solid-state lithium-sulfur battery prepared in this comparative example was tested by placing the battery in an oven at 25°C and performing a constant current charge and discharge test on a NEWARE battery test system. Fig.19 and Fig. 20 As shown in Figure 2, at 25°C, at a fixed discharge rate of 1C and a charge rate of 2C and 10C, the specific capacity is 1113 mAh·g -1 and 422mAh·g -1 .

[0225] The key parameters of each embodiment and each comparative example, as well as the electrochemical performance test results of the all-solid-state lithium-sulfur battery of each embodiment and each comparative example are shown in Table 1.

[0226] Table 1 Key parameters and electrochemical performance test results of each embodiment and each comparative example

[0227]

[0228]

[0229] As shown in Table 1, comparing Example 1 with Comparative Example 2 fully demonstrates that under normal temperature, the sulfur cathode prepared by the iodine-containing ion-conducting additive (LBPSI) not only has a high specific capacity, but also has a much higher cycle stability than the cathode prepared by the iodine-free ion-conducting additive Li 5.5 PS 4>5 Cl 1.5 Solid-state lithium-sulfur battery is prepared using sulfur positive electrode.

[0230] Comparison of Example 2 with Comparative Example 1, and Example 5 with Comparative Example 3 fully demonstrates that even at a high temperature of 60°C, the fast charging capability of the sulfur positive electrode prepared by the iodine-containing ion-conducting additive (LBPSI) is much greater than that of the sulfur positive electrode prepared by the iodine-free ion-conducting additive (Li 5.5 PS 4.5 Cl 1.5 ) of the sulfur cathode.

[0231] Comparison of Example 6 to Example 11 with Comparative Example 4 shows that, at room temperature, the iodine-containing ion-conducting additive (Li 2.29 P 0.66 S 2.65 I 0.29 , Li 3.5 B 1.67 S 3.5 I 1.5 , Li 2.29 P 0.66 As 0.1 S 2.9 I 0.29 , Li 2.29 P 0.66 Si0.05 S 2.75 I 0.29 , Li 5.4 PS 4.4 Cl 0.8 I 0.8 , Li 5.8 PS 4.8 Cl 0.6 Br 0.2 I 0.4 )'s sulfur positive electrode has a higher specific capacity than the solid-state lithium-sulfur battery made from Li3PS4 without iodine-conducting additives.

[0232] It can be seen from Examples 3 and 12 that even if the sulfur positive electrode is prepared by using a lower mass ratio of the iodine-containing ion-conducting additive LBPSI, that is, when the sulfur loading ratio is very high, the solid-state lithium-sulfur battery prepared therefrom still has a very high specific capacity and good cycle stability.

[0233] It can be seen from Example 4 that the sulfur positive electrode prepared by the iodine-containing ion-conducting additive LBPSI has a high specific capacity and good cycle stability at room temperature even at a high surface loading (i.e., sulfur content per square centimeter).

[0234] In summary, the iodine-containing ion-conducting additive plays the role of a redox medium in the sulfur cathode, effectively improving the reaction kinetics of lithium sulfide. At the same time, the reversible redox effect of the iodine-containing ion-conducting additive does not cause damage to the battery interface, and the battery has stable long-cycle performance.

[0235] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. Application of iodine-containing ion-conducting additive in sulfur positive electrode of solid-state lithium-sulfur battery, characterized in that: The iodine-containing ion-conducting additive acts as a redox mediator to promote the oxidation of Li2S, wherein during charging, I - The interface between the iodine-containing ion-conducting additive and the conductive material in the sulfur positive electrode is electrochemically oxidized to oxidized iodine, and then the oxidized iodine chemically oxidizes the Li2S in contact with it, and the redox-mediated process on the surface of the iodine-containing ion-conducting additive allows the reaction at the iodine-containing ion-conducting additive|Li2S two-phase interface to proceed, thereby improving the solid-state reaction kinetics of sulfur; The iodine-containing ion-conducting additive comprises a compound containing at least iodine, lithium and sulfur, and the molar amount of the iodine in each mole of the iodine-containing ion-conducting additive is n I is 0 <n I ≤2.

2. The use of the iodine-containing ion-conducting additive in the sulfur positive electrode of a solid-state lithium-sulfur battery according to claim 1, characterized in that: The iodine-containing ion-conducting additive comprises at least one compound of formula (1), formula (2), formula (3), formula (4), formula (5), formula (6) and formula (7): Formula (1): Li 2+y+z B 2x S 1+3x I y X z , where 0.15 ≤ x ≤ 4, 0 < y ≤ 2, 0 ≤ z ≤ 2, 0.05 ≤ y + z ≤ 2, and X includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN; Formula (2): Li 2+y P 2d S 1+5d I y , where 0.2≤d≤0.5, 0 <y≤2; Formula (3): Li 2+y P 2e Q 2f S 1+5e+5f I y , where 0.2 ≤ e ≤ 0.5, 0 < f ≤ 0.3, 0 < y ≤ 2, and Q includes at least one of the elements As, Sb, and Bi; Formula (4): Li 2+y P 2s Z g S 1+5s+2g I y , where 0.2 ≤ s ≤ 0.5, 0 < g ≤ 0.15, 0 < y ≤ 2, and Z includes at least one of the elements Si, Ge, and Sn; Formula (5): Li 2+y+c B 2b M 2a S 1+3b+5a I y A c , where 0.15 ≤ b ≤ 3, 0.05 ≤ a ≤ 3, 0.25 ≤ b + a ≤ 4, 0 < y ≤ 2, 0 ≤ c ≤ 2, 0 ≤ y + c ≤ 2, M includes at least one of P, As, Sb, and Bi; A includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN; Formula (6): Li 6-h PS 5-h Cl 1+h-y I y , where 0≤h≤2,0 <y≤2,1+h-y≥0; Formula (7): Li 6-m PS 5-m Cl 1+m-n-y Br n I y , where 0≤m≤2, 0≤n≤2, 0 <y≤2,1+m-n-y≥0。 3. The use of the iodine-containing ion-conducting additive in the sulfur positive electrode of a solid-state lithium-sulfur battery according to claim 2, characterized in that: At least one of the following conditions is met: (1) In the formula (1), 0.25≤x≤2, 0.01≤y≤2, 0.01≤y+z≤2; (2) In the formula (2), 0.25≤d≤0.5, 0.01≤y≤2; (3) In the formula (3), 0.25≤e≤0.5, 0 <f≤0.25,0.01<y≤2; (4) In the formula (4), 0.25≤s≤0.5, 0 <g≤0.125,0.01<y≤2; (5) In the formula (5), 0.25≤b≤2, 0.05≤a≤2, 0.3≤b+a≤3, 0.01≤y≤2, 0.01≤y+c≤2; (6) In the formula (5), 0.25≤b≤1.5, 0.05≤a≤1, 0.3≤b+a≤2.5, 0.01≤y≤2, 0≤c≤2, 0.01≤y+c≤2; (7) In the formula (6), 0≤h≤1, 0.01≤y≤2, 1+hy>0; (8) In the formula (7), 0≤m≤1, 0≤n≤1, 0.01≤y≤2, 1+mny>0.

4. The use of the iodine-containing ion-conducting additive in the sulfur positive electrode of a solid-state lithium-sulfur battery according to claim 1, characterized in that: The solid-state lithium-sulfur battery sulfur positive electrode also includes a sulfur-containing active material, and the sulfur-containing active material includes at least one of a sulfur element, a sulfur-selenium alloy, a composite material of sulfur and a carbon material, a composite material of sulfur and a metal sulfide, Li2S, a composite material of Li2S and a carbon material, a composite material of Li2S and LiI, and a composite material of Li2S and a metal sulfide; Preferably, the solid-state lithium-sulfur battery sulfur positive electrode further includes a conductive carbon additive; Preferably, the mass ratio of the sulfur-containing active material, the iodine-containing ion-conducting additive and the conductive carbon additive is 30-95:5-70:0-50.

5. A positive electrode material for a solid-state lithium-sulfur battery, characterized in that: The positive electrode material includes an iodine-containing ion-conducting additive, and the molar amount of iodine element in each mole of the iodine-containing ion-conducting additive is n I is 0 <n I ≤2, the iodine-containing ion-conducting additive comprises at least one compound of formula (1), formula (2), formula (3), formula (4), formula (5), formula (6) and formula (7): Formula (1): Li 2+y+z B 2x S 1+3x I y X z , where 0.15 ≤ x ≤ 4, 0 < y ≤ 2, 0 ≤ z ≤ 2, 0.05 ≤ y + z ≤ 2, and X includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN; Formula (2): Li 2+y P 2d S 1+5d I y , where 0.2≤d≤0.5, 0 <y≤2; Formula (3): Li 2+y P 2e Q 2f S 1+5e+5f I y , where 0.2 ≤ e ≤ 0.5, 0 < f ≤ 0.3, 0 < y ≤ 2, and Q includes at least one of the elements As, Sb, and Bi; Formula (4): Li 2+y P 2s Z g S 1+5s+2g I y , where 0.2 ≤ s ≤ 0.5, 0 < g ≤ 0.15, 0 < y ≤ 2, and Z includes at least one of the elements Si, Ge, and Sn; Formula (5): Li 2+y+c B 2b M 2a S 1+3b+5a I y A c , where 0.15 ≤ b ≤ 3, 0.05 ≤ a ≤ 3, 0.25 ≤ b + a ≤ 4, 0 < y ≤ 2, 0 ≤ c ≤ 2, 0 ≤ y + c ≤ 2, M includes at least one of P, As, Sb, and Bi; A includes at least one of F, Cl, Br, BH4, CN, OCN, and SCN; Formula (6): Li 6-h PS 5-h Cl 1+h-y I y , where 0≤h≤2,0 <y≤2,1+h-y≥0; Formula (7): Li 6-m PS 5-m Cl 1+m-n-y Br n I y , where 0≤m≤2, 0≤n≤2, 0 <y≤2,1+m-n-y≥0。 6. The positive electrode material for solid-state lithium-sulfur battery according to claim 5, characterized in that: The positive electrode material also includes a sulfur-containing active material; Preferably, the sulfur-containing active material includes at least one of elemental sulfur, sulfur-selenium alloy, a composite material of sulfur and carbon material, a composite material of sulfur and metal sulfide, Li2S, a composite material of Li2S and carbon material, a composite material of Li2S and LiI, and a composite material of Li2S and metal sulfide; Preferably, the positive electrode material further includes a conductive carbon additive; Preferably, the mass ratio of the sulfur-containing active material, the conductive carbon additive and the iodine-containing ion-conducting additive is 30-95:0-50:5-70; Preferably, the conductive carbon additive includes at least one of Ketjen black, conductive carbon black, vapor-grown carbon fiber reinforcement, carbon nanotubes, mesoporous carbon, microporous carbon, graphene and acetylene black.

7. The method for preparing a positive electrode material for a solid-state lithium-sulfur battery according to claim 6, characterized in that: The method comprises the following steps: mixing an iodine-containing ion-conducting additive with a sulfur-containing active material, or mixing an iodine-containing ion-conducting additive with a sulfur-containing active material and a conductive carbon additive; Preferably, the mixing method comprises at least one of grinding, ball milling, vibration milling and high-speed stirring.

8. A solid-state lithium-sulfur battery, characterized in that: Comprising the positive electrode material for a solid-state lithium-sulfur battery as claimed in claim 5 or 6.

9. The solid-state lithium-sulfur battery according to claim 8, characterized in that: The solid-state lithium-sulfur battery also includes a solid electrolyte separator and a negative electrode; Preferably, the negative electrode comprises at least one of lithium metal, lithium alloy, graphite, silicon, silicon-carbon composite material, silicon oxide and lithium carbon material; Preferably, the solid electrolyte separator includes at least one of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte, a polymer electrolyte, a sulfide-polymer composite electrolyte, a halide-polymer composite electrolyte and an oxide-polymer composite electrolyte.

10. An electrical device, characterized in that: Comprising the solid-state lithium-sulfur battery as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • Solid negative electrode additive for lithium-sulfur battery and preparation method of sulfur negative electrode containing solid negative electrode additive

    CN107834074A

  • Electrolyte solution containing iodide additives and sulfur dioxide-based secondary battery including the same

    CN107887646A

  • Composite gel electrolyte and preparation method and application thereof

    CN115966761A

  • Preparation method and application of iodide additive-introduced composite sulfur positive electrode

    CN118630131A

  • Positive electrode mixture and all-solid type lithium sulfur battery

    JP2015146281A

Cited By

  • A solid-state lithium-sulfur battery, including the positive electrode, a polyiodide additive, and its synthesis method.

    CN122725342A

  • Secondary battery

    WO2026138774A1